Health outcomes of children born after IVF/ICSI: a review of current expert opinion and literature. - Fauser, B; Devroey, P; Diedrich, K; Balaban, B; Bonduelle, M; Delemarre-van de Waal, H; Estella, C; Ezcurra, D; Geraedts, J; Howles, C; Lerner-Geva, L; Serna, J; et al. (2014)
The Sixth Evian Annual Reproduction (EVAR) Workshop Group Meeting was held to evaluate the impact of IVF/intracytoplasmic sperm injection on the health of assisted-conception children. Epidemiologists, reproductive endocrinologists, embryologists and geneticists presented data from published literature and ongoing research on the incidence of genetic and epigenetic abnormalities and congenital malformations in assisted-conception versus naturally conceived children to reach a consensus on the reasons for potential differences in outcomes between these two groups. IVF-conceived children have lower birthweights and higher peripheral fat, blood pressure and fasting glucose concentrations than controls. Growth, development and cognitive function in assisted-conception children are similar to controls. The absolute risk of imprinting disorders after assisted reproduction is less than 1%. A direct link between assisted reproduction and health-related outcomes in assisted-conception children could not be established. Women undergoing assisted reproduction are often older, increasing the chances of obtaining abnormal gametes that may cause deviations in outcomes between assisted-conception and naturally conceived children. However, after taking into account these factors, it is not clear to what extent poorer outcomes are due to the assisted reproduction procedures themselves. Large-scale, multicentre, prospective epidemiological studies are needed to investigate this further and to confirm long-term health consequences in assisted-conception children. Assisted reproduction treatment is a general term used to describe methods of achieving pregnancy by artificial means and includes IVF and sperm implantation. The effect of assisted reproduction treatment on the health of children born using these artificial methods is not fully understood. In April 2011, fertility research experts met to give presentations based on research in this area and to look carefully at the evidence for the effects of assisted reproduction treatment on children's health. The purpose of this review was to reach an agreement on whether there are differences in the health of assisted-conception children with naturally conceived children. The researchers discovered no increased risk in birth defects in assisted-conception children compared with naturally conceived children. They found that IVF-conceived children have lower birth weights and higher fat under the skin, higher blood pressure and higher fasting glucose concentrations than naturally conceived children; however, growth, development and cognitive function are similar between groups. A very low risk of disorders of genetic control was observed in assisted-conception children. Overall, there did not appear to be a direct link between assisted reproduction treatment and children's health. The researchers concluded that the cause of some differences in the health of children conceived using assisted reproduction treatment may be due to the age of the woman receiving treatment. Large-scale, research studies are needed to study the long-term health of children conceived using assisted reproduction treatment.